1987
DOI: 10.1093/ajcn/46.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Mineral balance in adult men: effect of four refined fibers

Abstract: Eleven men consumed a basal diet alone and with cellulose (Na-carboxymethylcellulose, locust bean gum, or karaya gum) added at 7.5 g fiber per 1000 calories for 4 wk each. Food, urine, and fecal composites were collected during the last 8 d of each feeding period. Bowel transit time was not significantly affected; however, total dry fecal weight was significantly increased after the refined fibers compared with that after the basal diet. Adding refined fibers to the basal diet did not significantly affect appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 18 publications
4
26
0
1
Order By: Relevance
“…The Ca, provided by this ®bre, increased the daily Ca intake by more than 30%, and that of Mg by about 20%. This con®rms previous data concerning the high participation of some crude ®bres in mineral intake (Van Dockkum et al, 1982;Behall et al, 1987;Fairweather-Tait et al, 1990). Furthermore, sugar…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The Ca, provided by this ®bre, increased the daily Ca intake by more than 30%, and that of Mg by about 20%. This con®rms previous data concerning the high participation of some crude ®bres in mineral intake (Van Dockkum et al, 1982;Behall et al, 1987;Fairweather-Tait et al, 1990). Furthermore, sugar…”
Section: Discussionsupporting
confidence: 91%
“…The effect of pectin on Zn retention had been tested in humans and found to be negligible (Lei et al, 1980). Finally in a similar study to ours, Behall et al (1987) found that re®ned ®bres had no effect on mineral balance in subjects consuming recommended dietary allowance levels of Fe and Zn when fed as part of their control diet.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, after feeding different fiber forms to adolescent males, Drews, et al [41] observed a decrease in copper balance among subjects that were fed hemicellulose, though pectin and intact cellulose had no effect on the copper concentration. Behall, et al [42] concluded that fiber forms such as locust bean, karaya gums, and carboxymethylcellulose, increased or had no effect on the trace mineral bioavailability, including copper. The absorption of copper follows a similar pathway as the absorption of calcium.…”
Section: Copper Absorptionmentioning
confidence: 99%
“…An effect of cellulose (14-23g/day) is demonstrated on increasing faecal weight in all trials. Two trials report an effect of cellulose on reducing intestinal transit time, but one trial reports no significant effect in subjects with a relatively fast initial intestinal transit time (Behall et al, 1987). The effect sizes are comparable to wheat fibre.…”
Section: Cellulosementioning
confidence: 94%
“…Three randomised controlled trials were identified that presented evidence on cellulose and in relation to faecal weight and transit times (Spiller et al, 1980;Hillman et al, 1983;Behall et al, 1987). The transit time methodologies were insufficiently comparable to allow a meta-analysis.…”
Section: Cellulosementioning
confidence: 99%